Comparative Effectiveness of Lifestyle Intervention on Fasting Plasma Glucose in Normal Weight Versus Overweight and Obese Adults With Prediabetes. Issue 3 (May 2022) - Salmon, Mandy K.; Gordon, Neil F.; Constantinou, Demitri; Reid, Kevin S.; Wright, Brenda S.; Kridl, Terri L.; Faircloth, George C.
Background . It is hypothesized that normal weight individuals develop diabetes through different pathophysiological mechanisms and that methods of prevention may differ in the absence of overweight/obesity. In this study, we compared the effect of lifestyle health coaching (LHC) on fasting plasma glucose (FPG) in normal weight, overweight, and obese US adults with prediabetes. Methods . Subjects were 1358 individuals who completed baseline and follow-up evaluations as part of an LHC program (follow-up = 6 months). Participants were stratified, based on baseline body mass index (BMI), into normal weight (n = 129), overweight (n = 345), and obese (n = 884) cohorts. LHC included counseling, predominantly via telehealth, on exercise and nutrition. Results . BMI decreased ( P < .001) in the overweight and obese participants but was unchanged in the normal weight participants. FPG decreased ( P < .001) in all 3 cohorts, and the magnitude of decrease did not differ significantly among cohorts. FPG decreased to <5.6 mmol/L in 58.1%, 49.3%, and 41.4% of the normal weight, overweight, and obese participants, respectively. Conclusions . To our knowledge, this study is the first outside of Asia to show that LHC is as effective in managing FPG in normal weight adults with prediabetes versus those who are overweight/obese.